Weight Loss in Midlife, Chronic Disease Incidence, and All-Cause Mortality During Extended Follow-Up - Strandberg, Timo E.; Strandberg, Arto Y.; Jyväkorpi, Satu; Urtamo, Annele; Nyberg, Solja T.; Frank Philipp; Pentti, Jaana; Pitkälä, Kaisu H.; Kivimäki, Mika (American Medical Association (AMA), 2025)
Importance: Few studies have examined long-term health benefits among individuals with sustained weight loss beyond its association with decreased diabetes risk.
Objective: To examine the long-term association of body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) changes during healthy midlife (ages 40-50 years) with later-life morbidity and mortality.
Design, setting, and participants: This cohort study analyzed data from 3 cohorts that included repeated height and weight measurements: the Whitehall II study (WHII; baseline, 1985-1988), Helsinki Businessmen Study (HBS; baseline, 1964-1973), and Finnish Public Sector study (FPS; baseline, 2000). Participants were categorized into 4 groups based on their first 2 weight assessments and followed up for morbidity and mortality outcomes. Data analyses were conducted between February 11, 2024, and February 20, 2025.
Exposures: Midlife BMI change was categorized as persistent BMI less than 25, BMI change from 25 or greater to less than 25, BMI change from less than 25 to 25 or greater, and persistent BMI of 25 or greater.
Main outcomes and measures: Incident chronic disease, including type 2 diabetes, myocardial infarction, stroke, cancer, asthma, or chronic obstructive pulmonary disease, was assessed in WHII and FPS, and all-cause mortality was assessed in HBS. These outcomes were obtained from linked electronic health records in national health registries.
Results: There were 23 149 participants, including 4118 men and women (median [IQR] age at first visit, 39 [37-42] years; 2968 men [72.1%]) from WHII, 2335 men (median [IQR] age at first visit, 42 [38-45] years) from HBS, and 16 696 men and women (median [IQR] age at first visit, 39 [34-43] years; 13 785 women [82.6%]) from FPS. During a median (IQR) follow-up of 22.8 (16.9-23.3) years, after adjusting for smoking, systolic blood pressure, and serum cholesterol at the first evaluation, WHII participants with weight loss had a decreased risk of developing chronic disease (hazard ratio [HR], 0.52; 95% CI, 0.35-0.78) compared with participants with persistent overweight. This finding was replicated after excluding diabetes from the outcome (HR, 0.58; 95% CI, 0.37-0.90). The corresponding HR in FPS was 0.43 (95% CI, 0.29-0.66) over a median (IQR) follow-up of 12.2 (8.2-12.2) years. In HBS, weight loss was associated with decreased mortality (HR, 0.81; 95% CI, 0.68-0.96) during an extended follow-up (median [IQR], 35 [24-43] years).
Conclusions and relevance: In this study, conducted when surgical and pharmacological weight-loss interventions were nearly nonexistent, sustained midlife weight loss compared with persistent overweight was associated with a decreased risk of chronic diseases beyond type 2 diabetes and decreased all-cause mortality.